A history of Queensland - Evans, Raymond, 1944- (Cambridge ; Port Melbourne : Cambridge University Press, 2007)
A History of Queensland is the first single volume analysis of Queensland's past, stretching from the time of earliest human habitation up to the present. It encompasses pre-contact Aboriginal history, the years of convictism, free settlement and subsequent urban and rural growth. It takes the reader through the tumultuous frontier and Federation years, the World Wars, the Cold War, the controversial Bjelke-Petersen era and on, beyond the beginning of the new millennium.
Includes bibliographical references (page 272-314) and index.
Keywords: Race relations - Violent - Massacres, murders, poisonings etc. - 1901-; History; Race relations - Violent; Government policy - State and territory - Queensland; Colonisation; Queensland -- History; Queensland -- History -- Textbooks; Queensland (Qld); Australian